Integrated GWAS, linkage, and transcriptome analysis to identify genetic loci and candidate genes for photoperiod sensitivity in maize - Jiang, Yulin; Guo, Shuang; Wang, Dong; Tu, Liang; Liu, Pengfei; Guo, Xiangyang; Wang, Angui; Zhu, Yunfang; Lu, Xuefeng; Chen, Zehui; Wu, Xun (Frontiers in Plant Science, 2024)
Maize photosensitivity and the control of flowering are not only important for reproduction, but also play pivotal roles in the processes of domestication and environmental adaptation, especially involving in the utilization strategy of tropical maize in high-latitude regions. In this study, we used a linkage mapping population and a inbred association panel with the photoperiod sensitivity index (PSI) phenotyped under different environments and performed transcriptome analysis of T32 and QR273 between long-day and short-day conditions. The results showed PSIs of days to tasseling (DTT), days to pollen shedding (DTP), and days to silking (DTS) were efficacious interactions with photoperiod sensitivity for maize latitude adaptation. A total of 48 QTLs and 252 QTNs were detected using the linkage population and the inbred association panel. 13 candidate genes were identified by combining GWAS approach, linkage analysis, and transcriptome analysis. Where in, five critical candidate genes of MYB163, bif1, burp8, CADR3, and Zm00001d050238, were significantly associated with photoperiod sensitivity. These results would provide much more abundant theoretical proofs to reveal the genetic basis of photoperiod sensitivity, which would be help to understand the genetic changes during domestication and improvement and contribute to reducing the barriers to use of tropical germplasm.